Evaluasi Model Countenance Stake Dalam Program Pelatihan Bagi Guru SD Mengaplikasikan Metode Pengajaran Bahasa : The Evaluation of Stake Countenance Model in a Training Program for Primary School Teachers by Applying Language Teaching Method - Dina Mardiana; Wagiran; Subyantoro (Jurnal Pendidikan Dasar dan Menengah, 2023)
This educational evaluation research aims at evaluating the training program in PKMS activity carried out at SD Muhammadiyah Pahandut, Palangkaraya. The training was provided to improve the ability of eleven classroom-teachers by using language teaching method in the learning of Indonesian language and literature at the elementary school. Evaluation of the program was carried out by a team of evaluators using the countenance stake model. Data were collected using techniques i.e., observation, document review, and interview. Then, being analyzed using case study analysis techniques by the descriptive qualitative method. From the results of the program evaluation, an average score of 4.8 was obtained, and it was categorized as a good quality of the implementation in the educational program. By the evaluation activity, the evaluator team has proven that the evaluation of the countenance Stake model can be carried out on an educational training program by a lecturer team from the university to the activity of community service (PKM).